Performance and usefulness of a novel automated immunoassay HISCL SARS-CoV-2 Antigen assay kit for the diagnosis of COVID-19 - Kaori Saito (Nature Portfolio, 2021)
Abstract Here, we aimed to evaluate the clinical performance of a novel automated immunoassay HISCL SARS-CoV-2 Antigen assay kit designed to detect the nucleocapsid (N) protein of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). This kit comprises automated chemiluminescence detection systems. Western blot analysis confirmed that anti-SARS-CoV antibodies detected SARS-CoV-2N proteins. The best cut-off index was determined, and clinical performance was tested using 115 serum samples obtained from 46 patients with coronavirus disease 2019 (COVID-19) and 69 individuals who tested negative for COVID-19 through reverse transcription quantitative polymerase chain reaction (RT-qPCR). The HISCL Antigen assay kit showed a sensitivity of 95.4% and 16.6% in samples with copy numbers > 100 and < 99, respectively. The kit did not cross-react with human coronaviruses causing seasonal common cold and influenza, and none of the 69 individuals without COVID-19 were diagnosed with positive results. Importantly, 81.8% of the samples with low virus load (< 50 copy numbers) were diagnosed as negative. Thus, using HISCL antigen assay kits may reduce overdiagnosis compared with RT-qPCR tests. The rapid and high-throughput HISCL SARS-CoV-2 Antigen assay kit developed here proved suitable for screening infectious COVID-19 and may help control the pandemic.